Load-Deflection Characteristics Of Steel, Polypropylene And Hybrid Fiber Reinforced Concrete Beams - Tamil Selvi M. (Archives of Civil Engineering, 2015)
Concrete is the most widely used construction material because of its specialty of being cast into any desired shape. The main requirements of earthquake resistant structures are good ductility and energy absorption capacity. Fiber reinforced concrete possesses high flexural and tensile strength, improved ductility, and high energy absorption over the conventional concrete in sustaining dynamic loads. The aim of this paper is to compare the properties of concrete beams in which three types of fibers are added individually. Steel fibers, polypropylene fibers and hybrid fibers were added to concrete in the weight ratio of four percentages in the preparation of four beam specimens. The fourth specimen did not contain fibers and acted as a control specimen. The dimensions of the beam specimens were 150 mm × 150 mm × 700 mm. The reinforced concrete beams of M30 grade concrete were prepared for casting and testing. Various parameters such as load carrying capacity, stiffness degradation, ductility characteristics and energy absorption capacity of FRC beams were compared with that of RC beams. The companion specimens were cast and tested to study strength properties and then the results were compared. All the beams were tested under three point bending under Universal Testing Machine (UTM). The results were evaluated with respect to modulus of elasticity, first crack load, ultimate load, and ultimate deflection. The test result shows that use of hybrid fiber improves the flexural performance of the reinforced concrete beams. The flexural behavior and stiffness of the tested beams were calculated, and compared with respect to their load carrying capacities. Comparison was also made with theoretical calculations in order to determine the load-deflection curves of the tested beams. Results of the experimental programme were compared with theoretical predictions. Based on the results of the experimental programme, it can be concluded that the addition of steel, polypropylene and hybrid fibers by 4% by weight of cement (but 2.14 % by volume of cement) had the best effect on the stiffness and energy absorption capacity of the beams.